ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIFITAS TERMINAL TIPE C - Sulistyowati Sulistyowati; Andar Sri Sumantri (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
Transportation includes several things in relation to moving from one place to another such as road infrastructure, modes of transportation, to the management of its management. The existence of the terminal cannot be separated from the transportation component, especially the public transportation system. The existence of terminals is often accused of being the cause of congestion, this is due to incomplete planning for land use patterns, road network patterns, population distribution patterns, movement needs, operational systems and service levels that lead to a low level of terminal effectiveness.This study aims to determine the effect of the role of the department of transportation, infrastructure, and employee performance on the effectiveness of the Magersari type C terminal in Magelang City. Data was collected using a research instrument in the form of a questionnaire. The sample in this study were 75 respondents, namely public transport drivers at the Magersari type C terminal. The method of analysis used multiple linear regression analysis. The regression formulation in this study is as follows:Y = 2,048 + 0,314X1 + 0,198X2 + 0,258X3 + µ. The results of multiple linear regression showed that there was a partial positive effect on the role of the transportation agency on the effectiveness of the terminal (tcount 3.195 > ttable 1.99346), infrastructure to the effectiveness of the terminal (tcount 2.598 > ttable 1.99346) and employee performance on the effectiveness of the terminal (tcount 2.882 > ttable 1.99346). The influence of the three research variables is very strong with the correlation coefficient of determination (Adjusted R2) = 0.538 which means that the variables of the role of the transportation service (X1), infrastructure (X2), and employee performance (X3) have an effect of 53.8% on the effectiveness of the terminal (Y ) and 46.2% (100% - 53.8%) influenced by variables outside this study.